Transcendence and sensoriness : perceptions, revelation, and the Arts - Christoffersen, Svein Aage, 1947-; Hellemo, Geir, 1950-; Onarheim, Leonora.; Petersen, Nils Holger.; Sandal, Margunn.; Hopenwasser, Frances E.; Teglbjærg, Leif Stubbe. (Studies in Religion and the Arts, 2015)
Protestant theology and culture are known for a reserved, at times skeptical, attitude to the use of art and aesthetic forms of expression in a religious context. In Transcendence and Sensoriness , this attitude is analysed and discussed both theoretically and through case studies considered in a broad theological and philosophical framework of religious aesthetics. Nordic scholars of theology, philosophy, art, music, and architecture, discuss questions of transcendence, the human senses, and the arts in order to challenge established perspectives within the aesthetics of religion and theology.